Spirituality as a Positive Youth Development Construct: A Conceptual Review - Daniel T. L. Shek (The Scientific World Journal)
The concept of spirituality as a positive youth development construct is reviewed in this paper. Both broad and narrow definitions of spirituality are examined and a working definition of spirituality is proposed. Regarding theories of spirituality, different models pertinent to spiritual development and the relationship between spirituality and positive youth development are highlighted. Different ecological factors, particularly family and peer influences, were found to influence spirituality. Research on the influence of spirituality on adolescent developmental outcomes is examined. Finally, ways to promote adolescent spirituality are discussed.